COVID-19 Challenge: What Has Been Done and What Must Be Done? - I. G. Belenkiy (Travmatologiâ i Ortopediâ Rossii, 2020)
The sequence of systemic measures to combat the COVID-19 pandemic in Russia is described. Some other countries experience of providing the specialized trauma care in a pandemic has been summarized. Almost everywhere, strict measures of infection prevention and treatment were introduced in stages. To date, there are the following generally accepted measures: discontinuation of planned surgeries, screening of emergency patients on COVID-19 with the subsequent separation of patient flows, the maximum reduction of hospital stay length. The special attention should be paid to personal protective equipment. The organizational and medical measures necessary for prevention of such pandemics in the future are described, namely equipping sanitary triage posts, creating a stock of personal protective equipment and disinfectants, developing a plan for transforming general hospitals into hospitals for infectious patients with the allocation of a primary patient reception post and their subsequent distribution into the green or red zones. The importance of pre-operative bed day reduction, telemedicine technologies and the need of healthcare financing increase to solve the tasks are substantiated.